Study The Effect Of Developing Explosive Power Using Weight Training On Pivot Correction Technique For Handball Players, Championship Center, Men Senior, For The 2019-2020 Sports Season An Experimental Study Of The Teams Participating In The National Han - Oulmane , Ryad (sports creativity, 2025)
The Object of the study aims to identify Developing explosive power by using weight training on correction technique from pivoting of handball players, for this purpose, we used the experimental method, On a sample composed of 20, probability randomly, and for data collection, we used a Tests For the lower limbs, And the upper limbs, test the shot force of the skill of correction from the thrust, After collecting the results and having treated them statistically System SPSS, we conclude the Evolution of the explosive force characteristic by using Weight training And its effect on the shooting skill from pivoting of the senior class handball players